Pengembangan Modul Berbasis Etnomatematika pada Songket Minangkabau di Fase F Jurusan Kesehatan SMAN 1 Kecamatan Lareh Sago Halaban - Yopita Yonanda; Isnaniah Isnaniah; M. Imamuddin; Arifmiboy Arifmiboy (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research was motivated by the lack of teaching materials that align with the characteristics and needs of students. One of the main issues identified is the use of learning modules that are not yet adapted to local culture and fail to provide meaningful learning experiences. To address this problem, the researcher developed a culturally based module inspired by Minangkabau songket. This study employed a Research and Development (R&D) design following the development stages proposed by Sugiyono. The results show that the developed module achieved a validity level of 82.58% (categorized as very valid), a practicality level of 87.6% (very practical), and an effectiveness level of 83.3% (very effective). Based on these findings, it can be concluded that the ethnomathematics-based module on Minangkabau songket for Phase F of the Health Department at SMAN 1 Lareh Sago Halaban in the 2023/2024 academic year meets the criteria of being valid, practical, and effective. Therefore, it is considered suitable for use as a culturally contextual teaching material that integrates local values into the learning process.